Enhancing three phenolic fractions of oats (Avena sativa L.) and their antioxidant activities by solid-state fermentation with Monascus anka and Bacillus subtilis. (May 2020) - Chen, Gong; Liu, Yan; Zeng, Jiarui; Tian, Xiaofei; Bei, Qi; Wu, Zhenqiang
Abstract: This work aims to improve phenolic fractions of oats and their antioxidant activities by solid-state fermentation (SSF) combining Monascus anka with Bacillus subtilis . Results revealed that the fermentation system significantly ( p < 0.05) increased the total phenolic content (TPC), which was 23-fold over that in unfermented oats. The hydrolytic enzyme activities of α-amylase, β- glucosidase, and cellulase were significantly (r > 0.75, p < 0.05) correlated to the TPC, indicated an important role in the release of phenolic in oats. The proportion of free phenolic fraction in oats was increased from 39.76% to 61.62%, while that of bound phenolic fraction decreased from 42.17% to 22.78%. Moreover, the phenolic compositions of free, conjugated and bound phenolic fractions varied with fermentation. It implied that the phenolic compounds in different forms could be converted and transformed in the SSF system. Meanwhile, the DPPH· and ABTS ·+ scavenging activities of the free and conjugated phenolic fractions in oats became stronger after fermentation. It indicated that the changes of antioxidant activities of phenolic fractions might be closely related to the structural modification by microbial enzymes in the SSF system. Consequently, this study provides a prospect fermentation process for improving the phenolic release and antioxidant activities in oats. Graphical abstract: Image 1 Highlights: SSF with Monascus anka and Bacillus subtilis much improves total phenolic content in oats. The inoculation moment of B. subtilis is a key factor of phenolic increase in the SSF system. The α-amylase, β- glucosidase, and cellulase play an important role in phenolic release in oats. The proportion of free, conjugated and bound phenolic fraction is much changed by SSF. Phenolic conversion by SSF shows great DPPH· and ABTS ·+ scavenging activities.